Pregnancy-related pelvic girdle pain: a need for increased awareness among healthcare professionals. (16th November 2010) - Bird, A; Woodcock, D; Candelier, C
Abstract : In 2005, an audit on the management of pregnant women with pelvic girdle pain (PGP) recommended a need for local guidelines, patient information leaflets, early referral to an obstetric physiotherapist with specific care plans in the women's maternity notes. Following implementation, an audit was carried out between July 2008 and March 2009. 276 women were referred to the physiotherapist. 13 women were diagnosed with PGP (1:250 incidence) – diagnostic criteria: presence of functional and objective asymmetry in the sacroiliac joints and/or symphysis pubis joint with or without restricted hip abduction. In 2005, the incidence was 1:32, subjective diagnostic criteria only were used. A range of interventions was offered to the women. An obstetric alert form with care plan for labour, delivery and post partum was completed and put in the notes. PGP was the indication for induction of labour in three women; in the four women delivered by elective Caesarean section, PGP was not the primary indication. Two of nine labouring women had pain free range of hip abduction measured and position in labour recorded. No women had their position for vaginal examinations and for delivery documented. Post partum, no women received regular analgesia, bed rest for 24–48 h or thromboprophylaxis unless delivered by Caesarean section. PGP lacks accurate diagnostic criteria and is poorly managed due to lack of awareness among healthcare professionals on treatment modalities. Women suffering from PGP are not receiving optimal care – care pathways must be followed to reduce morbidity in this common condition with a high recurrence rate in future pregnancies.